Remote Medical Monitoring System in Wireless Sensor Networks - Zhang, Chao (International Journal of Online and Biomedical Engineering (iJOE), 2016)
In order to solve the problem of monitoring remote medical care to identify good medical services, a medical service recommendation system based on privacy-preserved reputation scoring is designed. This system enables medical service users to get a reputation score of a Medical Service Provider before engaging in any services. The experiment results show that the proposed scheme is significantly more efficient in batch verification of digital signatures, making it a suitable practical solution to Mobile Health Care applications, while the third solution shows that the system is able to provide reputation scores as well as recommendation while preserving privacy as desired.